Interpolation of multi-LPV control systems based on Youla–Kucera parameterization. (December 2021) - Atoui, Hussam; Sename, Olivier; Milanes, Vicente; Martinez, John J.
Abstract: This paper presents a methodology which considers an interpolation between Linear Parameter-Varying (LPV) controllers that were designed separately for different objectives. The quadratic stability of the closed-loop system is proved under arbitrary interpolation in terms of a set of Linear Matrix Inequalities (LMIs). The interpolation strategy is based on Youla–Kucera (YK) parameterization. The proposed method can help multi-variable and multi-objective systems, to achieve high performances at different critical situations regardless of the interpolation rate.